Evaluation of a modified field school approach in knowledge appropriation by arracacha growers - Navarro Niño, Diego Alberto; Villamil Carvajal, Jorge Enrique; Garnica Montaña, Johanna Paola; Jaramillo Barrios, Camilo Ignacio (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The Farmer Field Schools (FFS) are a rural extension strategy and means of disseminating management practices and innovations to strengthen knowledge, emphasizing learning processes with a horizontal and two-way exchange of experiences between the facilitator and the farmers. This study aimed to evaluate a modified field school approach (MFFSA) for farmers in Cajamarca, Tolima - Colombia, with the purpose of identifying the knowledge acquired by farmers in agronomic issues related to production, nutrition, and pest and disease management, for a new arracacha cultivar called AGROSAVIA LA 22. The study simplified the traditional components of an FFS in preparation, implementation, and evaluation where new intervention strategies were incorporated. The results showed that when comparing the before and after of the intervention in the learning process, where a paired t-test was applied in a general way for four categories, it was found that the knowledge of the farmers of the three localities presented statistical differences (p <0.05) in the learning process, going from 36% to 70% in the four categories evaluated. It is concluded that the MFFSA are a promising and effective strategy to increase the knowledge of arracacha growers about innovations and cultivation practices, thus contributing to improve the processes of diffusion of innovations at the local level and strengthening rural extension processes.